Teachers with the magic: great teachers change students’ lives - Norton, M. Scott (Rowman & Littlefield Publishers, 2015)
This book centers on the fact that needed improvements in our schools will not occur unless education is able to attract and retain great teachers in the school's classrooms.Teachers with The Magic is directed to administrative leaders as well as those individuals that are seeking ways to become better teachers.